How Russia Affects the Neighborhood : Trade, Financial, and Remittance Channels - Espinosa-Bowen, Jaime (IMF Working Papers; Working Paper ;, 2009)
We test the extent to which growth in the 11 CIS countries (excluding Russia) was associated with developments in Russia, overall, as well as through the trade, financial and remittance channels over the last decade or so. The results point to the continued existence of economic links between the CIS countries and Russia, though these links may have altered since the 1998 crisis. Russia appears to influence regional growth mainly through the remittance channel and somewhat less so through the financial channel. There is a shrinking role of the trade (exports to Russia) channel. Russian growth shocks are associated with sizable effects on Belarus, Kazakhstan, Kyrgyz Republic, Tajikistan, and, to some extent, Georgia.